Markedly Enhanced Immunogenicity of a Pfs25 DNA-Based Malaria Transmission-Blocking Vaccine by In Vivo Electroporation - LeBlanc, Ralph (2007)
Pfs25 is a promising target antigen for the development of a malaria transmission-blocking vaccine and prior research has demonstrated induction of high and functionally effective antibodies in mice with IM injection of Pfs25 encoding DNA plasmid. Likewise, Pfs25 DNA vaccine was immunogenic in rhesus macaques but required a protein boost to elicit significant transmission blocking antibodies. The translation of these encouraging findings to human clinical trials has been impeded largely by the relatively poor immunogenicity of DNA plasmids in larger animals. In vivo electroporation (EP) has revealed significant enhancement of the potency of DNA plasmids. The results reported here compared the immunogenicity and functional transmission-blocking effects of immunization with DNA plasmid (25μg) by the traditional IM route compared to coupling the IM injection (0.25μg, 2.5μg and 25μg doses) with in vivo EP. Significantly, a 0.25μg dose of DNA plasmid, when administered with EP, induced antibody titers (1:160,000) and functional transmission blocking effects that were equivalent to those achieved by a one hundred fold higher (25 μg) dose of DNA plasmid given without EP. At a 25.0μg DNA dose with or without EP there was sufficient antigenic stimulation to result in effective antibody titers; however EP method yielded antibody titer of 1:1,280,000 as compared to only 1:160,000 titer without EP. This observed two log reduction in the amount of DNA plasmid required to induce significant transmission-blocking effects makes a compelling argument in favor of further evaluation of DNA vaccines by in vivo EP method in larger animals. Further experiments in non-human primates and eventually in phase I human trials will determine if the use of EP will induce effective and sustained malaria transmission blocking effects at acceptable doses of plasmid DNA.